Employment equity and mental health conditions: what affects Singaporeans' willingness to work with people with schizophrenia and people with depression? - Cheang, Anna Xin Hui (Nanyang Technological University, 2022)
People with mental health conditions such as depression or schizophrenia may face difficulties maintaining employment, but to what extent is this a result of social perceptions and stigmas surrounding these conditions? What affects the willingness of people to work with people with mental health conditions? This paper seeks to address these questions within the Singaporean context using a vignette experiment. Findings suggest that one’s level of stigma and willingness to work with individuals with mental health conditions are directly related. Singaporeans are more willing to work with People with Depression rather than People with Schizophrenia. In addition, one’s literacy about and personal exposure to these conditions do not affect one’s willingness to work with them, although one’s level of personal belief in the importance of employment equity functions as a better predictor of willingness. These indicate that more resources need to be devoted to address the greater stigma borne by People with Schizophrenia, and that public education efforts should be focused on instilling beliefs of equity rather than increasing literacy.